STRATEGI DIVERSIFIKASI PORTOFOLIO: ANALISIS DAMPAK RISIKO DAN KEUNTUNGAN PADA BANK KONVENSIONAL DAN SYARIAH MILIK NEGARA DI INDONESIA: (PORTFOLIO DIVERSIFICATION STRATEGIES: ANALYZING RISK AND RETURN IMPACTS IN INDONESIAN STATE-OWNED CONVENTIONAL AND ISLAMIC BANKS) - Kholidah, Himmatul; Maulidiyah, Maulidiyah; Hijriah, Hanifiyah Yuliatul; Md. Sahiq, Aqilah Nadiah (UPT Penerbitan Universitas Jember, 2024)
This research examines the relationship between credit portfolio diversification and the risk and return of state-owned banks (Bank BUMN) from 2019 to 2023. Using multiple linear regression analysis, it evaluates the impact of the Herfindahl Hirschman Index (HHI) on credit or financing risk (NPL and NPF) and bank returns (ROA, ROE) among state-owned banks listed on the Indonesia Stock Exchange. Control variables include bank size, loan or financing to deposit ratio (LDR and FDR), and equity to total asset ratio (ETA). The results show that credit portfolio diversification reduces credit risk in BUMN banks, suggesting that spreading credit exposures across sectors can mitigate risk. However, diversification does not significantly affect bank returns (ROA, ROE). Control variables such as bank size, LDR and FDR, and ETA show no significant impact on credit risk, ROA, or ROE. This study provides empirical evidence on the effectiveness of financing portfolio diversification in managing credit risk within state-owned banks, considering Islamic banking principles. While diversification can mitigate credit risk, its impact on profitability requires careful consideration. BUMN banks should implement robust risk assessment frameworks and strategic oversight to maximize diversification benefits while maintaining financial stability and adhering to ethical and Sharia-compliant financial practices.